2018
DOI: 10.1016/j.measurement.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

On the temporal analysis of acoustic waves using schlieren imaging

Abstract: The primary objective of the present study was to develop a quantitative schlieren-imaging technique that can be used to study the dynamics of instability waves. The technique was initially validated by optically capturing a controlled acoustic wave generated by a compression driver and excellent agreement was obtained with microphone measurements. An underexpanded jet was considered as an ideal test case due to the complexity and multitude of instability mechanism. Further analysis of the underexpanded jet de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A second important problem, as already anticipated, is the coexistence of hydrodynamic and acoustic flow fluctuations of very different scales in the same medium. A clear visualization of the coexistence of flow-based and acoustic pressure (or density) fluctuations in a medium can be found in figure 3, including the flow field from a jet, together with other interesting examples from daily life [13,14]. The work of Chu and Kovásznay [15] further clarifies the problem, by carrying out a disturbance analysis on Lighthill's aeroacoustic analogy.…”
Section: The Physics Behind the Measurement Problemmentioning
confidence: 94%
See 1 more Smart Citation
“…A second important problem, as already anticipated, is the coexistence of hydrodynamic and acoustic flow fluctuations of very different scales in the same medium. A clear visualization of the coexistence of flow-based and acoustic pressure (or density) fluctuations in a medium can be found in figure 3, including the flow field from a jet, together with other interesting examples from daily life [13,14]. The work of Chu and Kovásznay [15] further clarifies the problem, by carrying out a disturbance analysis on Lighthill's aeroacoustic analogy.…”
Section: The Physics Behind the Measurement Problemmentioning
confidence: 94%
“…Reproduced with permission from Dr Tuinstra (www.nlr.org/research-infrastructure/aeroacoustic-wind-tunnel/). (11) Reproduced with permission from[50] (13). Reproduced from[65].…”
mentioning
confidence: 99%
“…Because this is the fundamental topic of interest in the field of aeroacoustics, further study on the mechanism of screech-tone generation [8] [9], selection mechanism of oscillation modes [10] [11] [12] [13], and the shock-cell structure in the jet [14] [15] are investigated experimentally. Furthermore, the flow characterizations of screeching jet were performed by introducing the particle image velocimetry [14] and frequency analysis by high-speed schlieren imaging [15]. Note that these characteristics of screech tone were well reproduced in the numerical simulations [16] [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hypersonic boundary layer receptivity under free-stream disturbance refers to the process that occurs when disturbances in the free-stream enter the boundary layer and result in the generation of perturbations in the boundary layer. Many scholars have researched hypersonic boundary layer receptivity [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], but it is not yet fully understood because the hypersonic boundary layer receptivity is affected by many factors. These factors interact with each other, which increases the complexity of the hypersonic boundary layer receptivity.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the dominant mode of the acoustic waves in free-stream occurs in a lower frequency region, a larger spatial extent, and a smaller bulk propagation speed. Jagadeesh et al [ 9 ] used the Schlieren imaging technique to measure the unstable motion of acoustic waves in the boundary layer and reported that this method could be used to study laminar-turbulent transition and the flow in a large gradient region. Compared with acoustic waves, the influence of other types of free-stream disturbance on hypersonic boundary layer is less studied.…”
Section: Introductionmentioning
confidence: 99%